Iodine-catalyzed oxidative amination of sodium sulfinates: A convenient approach to the synthesis of sulfonamides under mild conditions - Chonchanok Buathongjan (2018)
© 2015 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. The iodine-catalyzed oxidative amination of sodium sulfinates in the presence of sodium percarbonate as the oxidant has been developed. The reaction shows good substrate scope and tolerates a wide range of functionalities in both amine and sodium sulfinate substrates. Aliphatic amines, heteroaromatic amines and hydrochloride salts of amines canbe employed as the amine sources in this transformation. Mechanistic studies indicated that a radical pathway might be involved in the reaction process. This transition-metalfree protocol offers an alternative and convenient approach for a preparation of a series of sulfonamides in moderate to good yields under mild conditions.